Correlation between relative age-standardized mortality rates and COVID-19 mortality over time in Italy: COVID-19 excess mortality - Mattiuzzi, Camilla; Henry, Brandon M.; Lippi, Giuseppe (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: This study was planned to estimate the contribution of coronavirus disease 2019 (COVID-19) related mortality on excess deaths recorded in Italy since the beginning of the pandemic. Methods: Official data on weekly number of COVID-19 related deaths in Italy were retrieved from the website of the Italian Ministry of Health, whilst information on weekly relative age-standardised mortality rates (rASMRs) in Italy during the COVID-19 pandemic was downloaded from the UK Office for National Statistics website. Univariate and multivariate correlation was conducted to explore the association between these two variables throughout the pandemic. Results: Significant univariate correlation was found between rASMR and number of official COVID-19 related deaths throughout the pandemic period. Such correlation was especially high during predominance of pre-Alpha and Alpha variants, remained significant during Delta variant predominance, but become no longer significant during Omicron variant predominance. In multivariable analysis, we estimated that COVID-19 may have contributed to 72% of the excess mortality recorded in Italy throughout the pandemic. The impact was higher during pre-Alpha and Alpha periods (i.e., 78% and 89%, respectively), decreased to 41% during Delta variant predominance, and became no longer significant after emergence of the Omicron variant. Conclusions: These results would suggest that COVID-19 may have largely contributed to excess mortality in Italy until the recent emergence of the Omicron variant, by which time previous loss of vulnerable people and radical changes in delivering healthcare may have paradoxically contributed to improve the cumulative death rate in the country.